Managing the shared accommodation industry ethical dilemmas : the case of Cape Town and eThekwini’s competing multi-stakeholder interests - Holtzhausen, Natasja (University of Pretoria, 2024)
Thesis (PhD (Business Management))--University of Pretoria, 2023.